Management of thumb tip injuries - Germann, Günter; Sauerbier, Michael; Rudolf, Klaus D.; Hrabowski, Manuel (The journal of hand surgery. [American volume], 2015)
The management of thumb tip injuries has undergone great changes in recent years. The traditional armamentarium of flaps has been expanded and replaced by a wide variety of flaps with more versatility and less donor side morbidity. Parallel to the development of new flaps, the conservative treatment of thumb tip injuries with semi-occlusive dressing has gained ground in the treatment of these injuries. Although tedious and time-consuming, and requiring intensive communication with the patient to explain the look and occasionally fetid smell of the wound, this technique yields excellent results with respect to restoring contour and sensibility in pulp injuries. The article gives an update on the current options for treating thumb tip injuries including the most commonly applied flaps.